Building bridges: HCI, visualization, and non-formal modeling : IFIP WG 13.7 Workshops on Human-Computer Interaction and Visualization: 7th HCIV@ECCE 2011, Rostock, Germany, August 23, 2011, and 8th HCIV@INTERACT 2011, Lisbon, Portugal, September 5, 2011, Revised Selected Papers - van der Veer, Gerrit C.; Domik, Gitta; Gershon, Nahum D.; Scheler, Inga; Ebert, Achim (Lecture Notes in Computer Science, 2014)
This volume constitutes the refereed post-workshop proceedings of two IFIP WG 13.7 workshops on Human-Computer Interaction and Visualization: the 7th HCIV Workshop on Non-formal Modelling for Interaction Design, held at the 29th European Conference on Cognitive Ergonomics, ECCE 2011, in Rostock, Germany, in August 2011 and the 8th HCIV Workshop on HCI and Visualization, held at the 13th IFIP TC 13 Conference on Human-Computer Interaction, INTERACT 2011, in Lisbon, Portugal, in September 2011. The 15 revised papers presented were carefully reviewed and selected for inclusion in this volume. They cover a wide range of topics in the fields of non-formal modeling, visualization and HCI and provide visions from researchers working at or across the borders between these domains that may help develop a holistic cross-discipline.